Gerakan masyarakat hidup sehat melalui kegiatan olah raga di masa adaptasi kebiasaan baru - Soemardiawan Soemardiawan; Hermansyah Hermansyah; Muhamad Salabi; Nurdin Nurdin; Lalu Sapta Wijaya Kesuma; Jamaludin Jamaludin (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2021)
Basically, in life, sport is a basic need for every human being at this time. Doing sports can prevent various diseases, including obesity, diabetes, cancer, injuries, and osteoporosis. In addition, exercise is also known to reduce stress and anxiety, improve sleep quality and concentration levels, and increase self-confidence. During the current Covid-19 pandemic, exercise can be an alternative in maintaining immune conditions. Therefore, this service activity aims to build public awareness about the healthy living movement through sports activities. Partners in this activity are residents of the Lingkar Permai community, RT 06, totaling 20 people. The activity method is through the transfer of knowledge and practice, while the steps are 1) counseling, 2) practice, 3) mentoring, and 4) evaluation. The results of the activities include 1) the understanding of partners has increased after counseling, the increase has reached 58.06%, and 2) partners can do simple movements taught by the team. Assistance activities still need to be carried out continuously so that people are genuinely aware of healthy living